2011
DOI: 10.1084/jem.20102229
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT cells are required for airway inflammation induced by environmental antigens

Abstract: House dust contains antigens capable of activating mouse and human iNKT cells, contributing to allergen-induced airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
117
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 58 publications
4
117
0
Order By: Relevance
“…CD1-dependent immunomodulatory lipids have been identified in gut microbes (11,12), pollen (23), house dust (24), and in our work, cow's milk. We have previously demonstrated that cow's milk contains substantially more lipid antigen activity than human or mouse milk.…”
Section: Discussionmentioning
confidence: 50%
“…CD1-dependent immunomodulatory lipids have been identified in gut microbes (11,12), pollen (23), house dust (24), and in our work, cow's milk. We have previously demonstrated that cow's milk contains substantially more lipid antigen activity than human or mouse milk.…”
Section: Discussionmentioning
confidence: 50%
“…Flow cytometry and preparation of fluorochrome-conjugated αGalCer-loaded CD1d tetramers were performed as previously described (71 ) were isolated from spleen using a FACSAria cell sorter (BD Biosciences) and stored as cell pellets at -80°C. RNA was isolated from the frozen cell pellets using the RNeasy Mini Kit (QIAGEN), and…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, 5 × 10 5 /ml DCs, DCs-αGC, or DCs-αGC-ATL313 were cocultured with Vα14Vβ8.2 NKT cell DN3A4-1.2 hybridomas (1.2) in 96-well round-bottom plates, and supernatant IL-2 was measured by ELISA (eBioscience) according to published protocols (70). αGC-or αGC-ATL313-loaded B cells (A20) were also cocultured with NKT cells to test NKT cell response by measuring IL-2 levels.…”
Section: Or Moderate [28 Minutes] Ischemic Injury)mentioning
confidence: 99%